The morbidity spectrum of influenza, respiratory syncytial virus, human metapneumovirus and human parainfluenza virus in young children by age and country income level: A systematic review and meta-analysis - Lian He; Jitian Weng; Fuyu Zhu; Yuhe Zhang; Junru Chen; Shuting Chen; Miaojia Lu; Harish Nair; You Li; Xin Wang (International Journal of Infectious Diseases)
Background: Influenza virus (IFV), respiratory syncytial virus (RSV), human metapneumovirus (hMPV) and parainfluenza virus (hPIV) cause substantial disease burden in children under 5 years, but the infection spectrum remains unclear. Methods: We systematically reviewed studies published between 1995 and 2023 to estimate probabilities between viral test positivity, symptomatic infections, acute lower respiratory infections (ALRI), ALRI with chest-wall indrawing (CWI), ALRI hospitalization, and very severe ALRI – p(symptomatic | test positive), p(ALRI | symptomatic), p(CWI | ALRI), p(hosp | ALRI) and p(very severe | hosp). (PROSPERO CRD42024584039; CRD42023439269). Results: Based on 129 studies, we estimated that 67.7% of IFV test-positives were symptomatic and 16.2% of symptomatic IFV infections developed ALRI. In children under 2 years, 71.8% of RSV test-positives were symptomatic. Across the viruses, the estimated p(CWI | ALRI) and p(hosp | ALRI) were higher in infants than older children; between 2.6% and 41.2% of hospitalized children with ALRI were very severe, with higher estimates in low and lower-middle income countries. Conclusions: Infants and children under 5 years in low and lower-middle income countries are important risk groups for immunization due to their high vulnerability to severe outcomes. These findings provide critical data to support immunization assessment and development of immunization strategies.